A smartphone-based surface plasmon resonance platform. Issue 39 (25th September 2018) - Lertvachirapaiboon, Chutiparn; Baba, Akira; Shinbo, Kazunari; Kato, Keizo
Abstract : This review provides an overview of smartphone-based SPR platforms in both reflection and transmission configurations, typical setups, and examples of their use in the analysis of chemical and biological samples. Abstract : Surface plasmon resonance (SPR) originates from collective oscillation of electron density and associated electromagnetic field at a metal/dielectric interface. Reflection SPR, which includes prism-coupling and grating-coupling methods, and transmission SPR (TSPR) have been developed for use in a smartphone sensing platform. The strength of this approach relies on the SPR phenomenon: the strong electromagnetic oscillation of electrons that can occur at a metal/dielectric interface and is highly sensitive to changes in the localized dielectric on the metal surface. The observable SPR signals are strong enough to detect with a simple camera. By combining the SPR phenomenon with the high performance of a smartphone camera, smartphone-based SPR platforms have been developed for use in on-site and remote detection of biomedical and environmental samples, point-of-care devices, and practical use in household devices. This review gives an overview of smartphone-based SPR platforms in both reflection SPR and TSPR configurations, the design of the devices, and the typical setup used to acquire spectroscopic information and SPR images, as well as providing some examples of their use in the analysis of chemical and biological samples.